Strategi Pengembangan Kawasan dan Industri Halal - Cucun Cunayah; Imron Fathurohman; Nour Khalid; Hartono Hartono (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
The article aims to explain halal industry strategies and halal industrial areas. The method used in this article is a qualitative method, the data source for this research was obtained from written sources related to halal industrial strategies and halal industrial area strategies. The type of data used in this article is qualitative data. This data collection technique was carried out by collecting books and journals. The halal industry development strategy involves human resource development, socialization of halal certification, collaboration between stakeholders, and infrastructure development. Halal industrial areas also require a comprehensive strategy, including infrastructure development, education, research, promotion and partnerships